Analisis Komparatif Kinerja Saham Sebelum dan Sesudah Pengumuman Right Issue - Kusuma, Putu Sri Arta Jaya; Suryanawa, I Ketut (E-Jurnal Akuntansi; Vol 12 No 3 (2015), 2015)
Rights issue is the issuance of new shares by the company in which the right to buy new shares is granted to existing shareholders. Rights issue in Indonesia is better known as Pre-emption right (ER). This is done to provide an opportunity for existing shareholders to maintain its ownership percentage. The Announcement of rights issue may lead the market to react and affect the performance of the stock. This can lead to differences in the performance of the stock before and after the announcement of the rights issue in this study is proxied by abnormal stock returns and liquidity. The study was conducted on companies listed in Indonesia Stock Exchange (IDX) and the issuing rights issue in 2010-2013. This study sampled 91 announcement of the rights issue in 2010-2013. The analysis technique used is paired sample t-test. Based on this research, it is known that there is no difference abnormal returns before and after the rights issue, but there are differences in liquidity of shares before and after the announcement of the rights issue. This is due to the announcement of the rights issue has been known beforehand by the investor or leak information.
Keywords: right issue, abnormal return, stock liquidity